2019
DOI: 10.1111/jam.14194
|View full text |Cite
|
Sign up to set email alerts
|

A plant growth-promoting bacterium alters the microbial community of continuous cropping poplar trees’ rhizosphere

Abstract: Aims:We aimed to develop a biological agent that regulates the microbial community structure of the poplar rhizosphere and alleviates the effects of continuous poplar cropping. Methods and Results: Poplar rhizosphere soils were treated with or without Paenibacillus polymyxa CP-S316 microbial fermentation medium. Real-time polymerase chain reaction was performed to measure bacteria and fungi in both groups, and microbial communities were analysed by metabarcoding. In fungi, the operational taxonomic units, abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Therefore, the study of the microbial community structure and diversity in rhizosphere soil is valuable in understanding the mechanism of PGPR and in evaluating the optimal measures for increasing plant salt tolerance. The diversity of soil microbial community is closely related to crop growth and the prevention and control of soil-borne diseases ( Miransari, 2013 ; Sui et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the study of the microbial community structure and diversity in rhizosphere soil is valuable in understanding the mechanism of PGPR and in evaluating the optimal measures for increasing plant salt tolerance. The diversity of soil microbial community is closely related to crop growth and the prevention and control of soil-borne diseases ( Miransari, 2013 ; Sui et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cropping means that the same crop species or its relatives is sown on the same area of land over long-term. Even if the field management regime is good, the crop may still suffer from reduced crop growth and development, decreased yield quality, and an increase in disease ( Aparicio and Costa, 2007 ; Li et al, 2016 ; Sui et al, 2019 ; Liu et al, 2020 ). According to a recent study, the secretion of metabolites and leached substances from the plant increase under the CC system ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rhizosphere, the bacteria so called plant growth promoting rhizobacteria (PGPR) 5 could promote plant growth by various mechanisms, such as inhibiting phytopathogens, improving plant nutrient supply, producing phytohormones, and modifying physicochemical properties of soil 6 . On the other hand, PGPR also can affect the composition of microbial communities in the rhizosphere (rhizomicrobiome) of associated plants, which in turn affect the health of the entire soil microbiome 7,8 and affect the growth of plants. Zhang et al 9 identified a consortium of three PGPR strains (Bacillus cereus AR156, Bacillus subtilis SM21, and Serratia sp.…”
mentioning
confidence: 99%